Factors Associated with Exclusive Use of Hygienic Methods during Menstruation among Adolescent Girls (15–19 Years) in Urban India: Evidence from NFHS-5 - Roy, Doli; Kasemi, Nuruzzaman; Halder, Manik; Majumder, Malasree (Heliyon, 2024)
Menstrual hygiene is a critical public health concern for adolescent girls in urban India. However, there is a paucity of research on this subject, particularly on a national scale. To the best of our knowledge, this study diverges from previous research, as the majority of prior investigations in India have centered on rural locales, married individuals, and those aged between 15 and 24 years. Thus, this study aims to fill this gap by investigating the factors associated with the exclusive use of hygienic methods during menstruation among urban adolescent girls (15–19 years) in India. A total of 25136 samples were included in this analysis from the National Family Health Survey 5 (NFHS-5). The Binary logistic regression model has been administered to determine the associated factors of the exclusive use of hygienic methods among adolescent girls. The results of the multivariate model revealed significant positive associations between higher education levels and usage of menstrual hygiene management products (AOR: 1.860; 95 % CI: 1.418–2.439), (AOR: 2.110; 95 % CI: 1.553–2.867). Additionally, individuals in higher wealth quintiles were more likely to use MHM products, with the richest quintile showing the highest likelihood (AOR: 5.310; 95 % CI: 4.494–6.275). Attendance at cultural events such as cinema or theater was positively associated with MHM product utilization (AOR: 1.338; 95 % CI: 1.181–1.517). Conversely, Lack of access to sanitation facilities was inversely associated with MHM product utilization (AOR: 0.742; 95 % CI: 0.628–0.877). Muslim girls had lower odds than Hindus (AOR: 0.576; 95 % CI: 0.520–0.637). Substantial regional variations were evident, with the Western (AOR: 0.879; 95 % CI: 0.759–1.019), Eastern (AOR: 0.747; 95 % CI: 0.654–0.854), Central (AOR: 0.349; 95 % CI: 0.313–0.388), and North-eastern regions (AOR: 0.597; 95 % CI: 0.490–0.727) displaying diminished odds of MHM product usage relative to the southern region. General caste had higher odds compared to scheduled caste (AOR: 1.255, 95 % CI: 1.103–1.429), while other backward caste had lower odds (AOR: 0.858, 95 % CI: 0.771–0.955). These findings underscore the importance of addressing inequalities in access to menstrual hygiene products among urban adolescent girls in India. Targeted interventions and educational programs are essential to ensure equitable access and promote overall health and well-being.